MiRNA126 – RGS16 – CXCL12 Cascade as a Potential Mechanism of Acute Exercise-Induced Precursor Cell Mobilization - Schmid, Michelle; Martins, Helena Caria; Schratt, Gerhard; Kröpfl, Julia M.; Spengler, Christina M. (Frontiers in Physiology, 2021)
Acute exercise enhances circulating stem and precursor cells (CPCs) in the peripheral blood. The responsible mechanisms and molecular pathways, however, have not been fully identified. The aim of the present study was to investigate a pathway related to elevated levels of apoptotic peripheral blood mononuclear cells (MNCs) and their secretome. An increased uptake of miRNA126 in MNCs was suggested to lead to reduced levels of RGS16 mRNA and, in turn, an enhanced translation and secretion of CXCL12. Eighteen healthy, young men underwent two identical incremental cycling exercises of which the first served as control while the second was preceded by a 7-day-long antioxidative supplementation. Blood samples were collected at baseline (−10min) and several time points after exercise (0, 30, 90, 180, and 270min). Relative concentrations of miRNA126 in MNCs and CXCL12 levels in plasma were determined at all time points while RGS16 mRNA was assessed in MNCs at baseline and 30min after exercise. CXCL12 increased after exercise and strongly correlated with CPC numbers. MiRNA126 increased 30min and, to a lesser extent, also 180 and 270min after exercise but only with supplementation. RGS16 mRNA decreased 30min after exercise independent of the intervention. The amount of RGS16 mRNA inversely correlated with levels of miRNA126, but not with plasma CXCL12. In conclusion, even though plasma CXCL12 correlated with CPC numbers, the increase in CXCL12 cannot be explained by the increased concentration of miRNA126 and lower RGS16 mRNA in MNCs that would have allowed for an enhanced translation of CXCL12. Clinical Trial Registration: ClinicalTrials.gov, NCT03747913. Registered 20 November 2018, https://clinicaltrials.gov/ct2/show/NCT03747913.